PENINGKATAN PENDAPATAN PETERNAK MELALUI MANAJEMEN FEEDING PRACTICE DI KELOMPOK TERNAK ITIK USAHA BERSAMA DI DESA SIKABU-KABU KABUPATEN 50 KOTA - Sabrina Sabrina; Husmaini Husmaini; Kusnadidi Subekti; Firda Arlina (LPPM Universitas Andalas, 2024)
This activity aims to provide training and technology packages for improving the maintenance system, knowledge of feed ingredients, technology for producing duck feed based on local feed, restricted feeding. The ultimate goal of this activity is to increase egg production, productivity, feed cost efficiency in the context of developing and increasing farmers' income while forming / developing economically independent partner groups. This activity was carried out in Tanjung Haro Selatan, Luak District, 50 Kota Regency, West Sumatra. The partner involved in this activity is the